1980
DOI: 10.1093/bja/52.3.247
|View full text |Cite
|
Sign up to set email alerts
|

Observations on Extradural Morphine Analgesia in Various Pain Conditions

Abstract: We report the extradural administration of low-dose morphine in 10 ml of 10% dextrose (2-3 mg) to 98 adult patients with various types of acute and chronic pain. Extradural morphine injections were given either via a Tuohy needle (single or repeat injection) or via an extradural catheter. Pain relief was evaluated by subjective scoring and by the subsequent need for systemic analgesics. In 56% of patients, pain relief was considered good or excellent, in 24% it was fair, and in 20%, poor. The best results were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
3

Year Published

1981
1981
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(23 citation statements)
references
References 10 publications
1
19
0
3
Order By: Relevance
“…lO Boas places the incidence of significant side effects at 50070 including one cardio-respiratory arrest in 25 patients. lI Magora et al 5 report transient retention in three, dizziness and vomiting in two and accidental dural puncture in one of their 98 patients. Bromage et al 6 report no bladder problems at all and itching in one only, of their 67 patients.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…lO Boas places the incidence of significant side effects at 50070 including one cardio-respiratory arrest in 25 patients. lI Magora et al 5 report transient retention in three, dizziness and vomiting in two and accidental dural puncture in one of their 98 patients. Bromage et al 6 report no bladder problems at all and itching in one only, of their 67 patients.…”
Section: Discussionmentioning
confidence: 94%
“…Maximal effect appeared later, at 30 to 60 minutes when acute surgical pain was treated, although the pain of malignancy or ischaemia appeared to respond more rapidly. Magora et al ,5 reported the efficacy of 2 or 3 mg doses of morphine in relieving pain. In preliminary studies, we found that this was often inadequate for the treatment of postoperative pain and for this reason the minimum dose used in this study was 4 mg. Bromage et al 6 determined the effective analgesic dose of morphine to be 10.3 mg for upper abdominal surgery and 7.6 mg for lower abdominal surgery, whereas in our cases we found that 6 mg was generally sufficient to ensure good analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Pain relief after intrathecal [10,16,17] and epidural [1,3,6,9] injection of small doses of morphine is well known. The works of Snyder [12,13] and of Yaksh and Rudy [18] provide the pathogenetic basis for the marked effectivity of such small doses of morphine.…”
Section: Discussionmentioning
confidence: 99%
“…Pain occurs in 70°7o of patients with cancer, albeit not in all cases due to the tumor itself [14], The recommended treatment for bone pain due to metastases or to destruction of bone by tumor (without nerve-trunk compression) involves the administration of non-steroid antiinflammatory drugs (bone pain is attributable in part to OcO:oooooo õ ::::::::::::::::::::::::::::::::::::::::::::::::: a high local concentration of prostaglandins) and opioids [8,9,11,15]. Oral morphine may be given in a wide range of doses, from a little as 2.5 rag/day to 1000 rag/day [15].…”
Section: Discussionmentioning
confidence: 99%
“…At the time of administration of the epidural drug one hour postoperatively, all patients had regression of their sensorineural blockade. Magora et al 6 reported the efficacy of 3 mg doses of morphine in relieving pain but as these patients were unpremedicated a dose of morphine 5 mg sulphate was selected. Bromage et aC required a higher morphine dose from 7.6 mg to 10.3 mg but he was dealing with more painful procedures, such as upper abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%